Improving the quality of life of patients with stable angina pectoris using combined therapy - K. O. Zolotarova (Regulatory Mechanisms in Biosystems, 2017)
Treatment of chronic ischemic heart disease includes the use of non-drug methods (anti-hypodynamia, smoking cessation, etc.), as well as drug therapy, the main tasks of which are to reduce the risk of complications such as stroke, myocardial infarction, sudden cardiac death, and to gain an increase in life expectancy. An important aspect of treatment is also a decrease in the frequency and intensity of angina attacks, the need for short-acting nitrates, to gain an increase in physical activity, that is, an overall, improvement in the quality of life of patients. The article presents the results of studying the quality of life indicators of patients with stable angina pectoris with the use of omega-3 polyunsaturated fatty acids and magnetotherapy. 85 patients with stable angina pectoris were examined, divided into three groups according to the method of therapy. 28 patients of the I (control) group received a drug complex corresponding to the national protocol for the treatment of patients with angina pectoris: nitrates, beta-blockers, ACE inhibitors, antiplatelet drugs, statins (atorvastatin at a daily dose of 20 mg). 29 patients of the II group, together with protocol therapy, received the drug omega-3 polyunsaturated fatty acids in a daily dosage of 2000 mg, divided into 2 doses. In connection with the known hypolipidemic action of omega-3 PUFA, the daily dose of atorvastatin in this and the next group was reduced to 10 mg. Group III consisted of 28 patients who were prescribed omega-3 polyunsaturated fatty acids and a course of magnetotherapy according to a special method against the background of the protocol medication complex. It was revealed that, initially in patients with angina, the quality of life indicators according to the Seattle questionnaire and the visual analogue scale were reduced. It was shown that with the use of the protocol medication complex, all the parameters of the quality of life improved reliably, with a significant reduction in the angina pain scales and less significant improvement on the scales of physical activity, assessments of health and the perception of the disease . Upon adherence to the therapy of omega-3 polyunsaturated fatty acids, there was a positive but very weak tendency to improve the quality of life indicators, which did not differ significantly from the control. The use of combined therapy with simultaneous inclusion of omega-3 polyunsaturated fatty acids and magnetotherapy led to significant and reliable improvement in the quality of life indicators, not only on the scales reflecting the pain component, but also on the indicators that characterize the psychological contribution to the quality of life (treatment satisfaction and quality of life (disease perception)). The significant improvement in the quality of life in patients receiving magnetotherapy in contrast to the absence of such influence in patients receiving omega-3 polyunsaturated fatty acids without magnetotherapy was due to the strong antianginal effect of MT, its sedative and emotionally relaxing action, and the ability to enhance the effects of medications.